Explaining Changes in Tax Burdens in Latin America: Does Politics Trump Economics? - Mark Hallerberg; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2015)
This paper examines whether elections, which are generally held on fixed dates, and banking crises explain the timing of tax reforms and the allocation of the additional tax burden. Using an original fine-grained dataset of tax reforms, the paper finds support for the role of these two sources of variation. In particular, the probability of reform is higher during banking crises. During electoral periods, increasing taxes becomes highly unlikely, even if the government is facing financing problems. Interestingly, politics seem to trump economics: banking crises do not affect the probability of having a reform during electoral times. Moreover, the presence of an IMF program affects the tax instruments chosen: countries with a program increase the value-added tax, while those without raise the personal income tax. Finally, the ideology of the president does not explain who bears the additional tax burden.
hdl:11319/7205
Keywords: F41; H2; 330; Taxation; Banking crises; Elections; Political economy; Fiscal reform; Ideology; Policymaking